2013
DOI: 10.1002/oby.20330
|View full text |Cite
|
Sign up to set email alerts
|

BifidobacteriumCECT 7765 improves metabolic and immunological alterations associated with obesity in high-fat diet-fed mice

Abstract: Objectives: To evaluate the effects of administration of Bifidobacterium pseudocatenulatum CECT 7765 on metabolic and immune alterations in obese mice. Design and Methods: Adult male wild-type C57BL-6 mice were fed a standard diet or high-fat diet (HFD), supplemented or not with B. pseudocatenulatum CECT 7765 for 7 weeks. The assessments included biochemical and immunological parameters, insulin resistance, glucose tolerance, histology of liver, white-adipose and intestinal tissues, immunocompetent cell functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
148
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(158 citation statements)
references
References 39 publications
9
148
1
Order By: Relevance
“…The experimental studies [98][99][100][101][102][103][104] demonstrating the beneficial effects observed in HFD-induced metabolic syndrome, after the administration of probiotics containing Bifidobacterium strains, are reported in Table 1.…”
Section: Probioticsmentioning
confidence: 99%
“…The experimental studies [98][99][100][101][102][103][104] demonstrating the beneficial effects observed in HFD-induced metabolic syndrome, after the administration of probiotics containing Bifidobacterium strains, are reported in Table 1.…”
Section: Probioticsmentioning
confidence: 99%
“…Although not unanimously shown [10][11][12], on the one hand, obesity appears to be characterized by a decrease in Bacteroidetes and a corresponding increase in Firmicutes, which has been associated with increased energy extraction during digestion [13]. On the other hand, certain strains of bifidobacteria have been linked with improvements in metabolic health, including improved glucose tolerance, reduced serum cholesterol and triglycerides, and lower serum levels of leptin and interleukin 6 [14,15]. Although prebiotics are known to increase bifidobacteria and reduce Firmicutes [16,17], examination of the effects of other nondigestible carbohydrates, such as resistant starches and their fermentation end products (ie, short chain fatty acids [SCFAs]), are increasingly being examined for their effects on gut microbiota [18].…”
Section: Introductionmentioning
confidence: 97%
“…and decreased Firmicutes (53). Cano et al (59) reported that Bifidobacterium pseudocatenulatum consumption improved glucose tolerance and inflammatory status while decreasing serum LPS and hepatic steatosis in HFD-fed mice. Another study showed that prebiotic oligofructose in combination with probiotic Bifidobacterium animalis subsp.…”
Section: Introductionmentioning
confidence: 99%